Practices concerning management of Gartland type III supracondylar humeral fractures among Italian pediatric orthopedic surgeons. Issue 3 (May 2019) - Marengo, Lorenza; Cravino, Mattia; Origo, Carlo
Abstract : The purpose of this study was to investigate the current practice among Italian pediatric orthopedic surgeons concerning management of Gartland type III supracondylar humerus fractures (SHFs). A total of 17 Italian pediatric orthopedic surgeons were asked to complete a questionnaire about their attitudes and practices concerning Gartland type III SHF treatment in 2015. Overall, 67% of the fractures were treated in a delayed fashion (>6 h after patient presentation to the emergency department). Moreover, the method of fixation was lateral-only pinning (64% of the cases). Although the management of any child with a Gartland type III SHF should be individualized, this study shows that delayed surgery and lateral-only pin fixation is the preferred method for the treatment of most of these injuries.